Analisa Prosedur Tembakan Peringatan terhadap Keselamatan Petugas dan Publik - Muhammad Ichsan Rizal (Jurnal Syntax Admiration, 2024)
This study aims to analyze the warning firing procedure in the context of law enforcement in Indonesia, especially its impact on the safety of officers and the public. Warning shots are a form of use of non-lethal force regulated in Perkap No. 1 of 2009. While the goal is to mitigate the threat, the procedure often presents risks, such as the psychological impact on the suspect and the potential danger of falling bullets. The research method used is a qualitative-descriptive approach, with literature review and case study analysis of several incidents in Indonesia, including the panic incident in Bekasi. The results showed that while warning shots are effective in some situations to stop threats, they can also trigger unexpected responses such as panic that threaten public safety. In addition, the implementation of this policy is highly dependent on the understanding and discretion of officers in the field. This study recommends the use of non-lethal tools such as Taser and the application of de-escalation methods to reduce the risk. Intensive training for officers is also needed to improve decision-making abilities in emergency situations. The findings of this study are expected to be the basis for perfecting the policy on the use of force by the National Police to improve the safety of officers and the public.